Biochemical aspects of bacterial strategies for handling the incomplete translation processes - Shimizu, Yoshihiro (Frontiers in Microbiology, 2014)
During protein synthesis in cells, translating ribosomes may encounter abnormal situations that lead to retention of immature peptidyl-tRNA on the ribosome due to failure of suitable termination processes. Bacterial cells handle such situations by employing three systems that rescue the stalled translation machinery. The transfer messenger RNA/small protein B (tmRNA/SmpB) system, also called the trans-translation system, rescues stalled ribosomes by initiating template switching from the incomplete mRNA to the short open reading frame of tmRNA, leading to the production of a protein containing a C-terminal tag that renders it susceptible to proteolysis. The ArfA/RF2 and ArfB systems rescue stalled ribosomes directly by hydrolyzing the immature peptidyl-tRNA remaining on the ribosome. Here, the biochemical aspects of these systems, as clarified by recent studies, are reviewed.